Con Drury: philosopher and psychiatrist. Issue 4 (December 2017) - Hayes, John
Maurice O'Connor Drury (1907–76), an Irish psychiatrist, is best known for his accounts of his close friendship with the eminent twentieth-century philosopher, Ludwig Wittgenstein. His only book, The Danger of Words (1973), was well received by those who had an interest in the relationship between psychiatry, psychology and philosophy. This article concentrates on Drury's experiences, studies and writings in these fields.